Neurodevelopmental Status of Moderate to Late Preterm Infants at 6 Months Corrected Age - Hoq, Tanjina; Chowdhury, Pranab Kumar; Ahmed, Farid Uddin; Datta, Mitra; Hafiz, Promugdha; Das, Rita (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Moderate Preterm (MP) and Late Preterm (LP) infants together comprise more than 80% of all prematurely born infants. Since last decade, there has been growing concern about Neurodevelopmental Abnormality (NDA) in these infants. This study was aimed to assess neurodevelopmental status of moderate to late preterm born neonates and to determine factors associated with adverse neurodevelopmental outcome in a tertiary hospital in Bangladesh. Materials and methods: In this prospective observational study 215 preterm (32 to <37 completed weeks gestation at birth) infants (107 MP and 108 LP) were enrolled from the Special Care Neonatal Unit (SCANU) Chittagong Medical College Hospital from June 2018 to May 2019. Neurodevelopmental assessment was done by Rapid Neurodevelopmental Assessment (RNDA) at 1, 3 and 6 months of Corrected Age (CA). Results: Of the 215 enrolled children, 63 (29.3%) attended all the 3 follow-up, 123 (57.2%) had incomplete follow-up or lost and 29 (13.5%) died. At final follow-up out of 63 infants 43 (68.3%) had no abnormality in all 8 domains of RNDA. Seven infants (11.1%) had abnormality in one domain and 13 (20.6%) had abnormality in more than one domain. Gross motor abnormality was most common abnormality (28.6%), followed by cognition (14.3%), vision (12.7%) and behavior (12.7%). Small for gestational age and lower birth weight were found to be independent predictive factors for NDA in moderate to late preterm infants. Conclusion: Study has shown that NDA persist till 6 months of CA in moderate to late preterm infants. It is important to closely monitor the neurodevelopmental status and provide early intervention in referred cases. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 50-54